Penerapan Pendekatan Kooperatif Model Jigsaw terhadap Keaktifan Belajar Siswa - Riana Sinaga; M. Amin Fauzi (Journal on Education, 2024)
The aim of this study is to describe the impact of cooperative learning approaches with jigsaw types on student activity. Based on initial observations, the researchers found that students looked bored, inactive in learning, like lazy in answering questions, and embarrassed to express their opinions. This is due to some factors such as conventional learning, teachers dominating learning, the absence of learning media, as well as the lack of learning strategies given to students, such as jigsaw-type cooperative learning. This research uses an approach with a type of qualitative research that is descriptive, although data collection techniques are direct observations, interviews and documentation. Data analysis techniques use Milles and Huberman data analysis techniques that have three stages: data reduction, data presentation, and inference. Through this research, the results were obtained that student activity can be improved while following learning through collaborative jigsaw-type stimulation.